TITANIUM DIOXIDE NANOPARTICLES AND METAL-LOADED TITANIUM DIOXIDE NANOPARTICLES SYNTHESIZED BY THE MODIFIED SOL-GEL METHOD AND THEIR APPLICATIONS - Hathaithip Ninsonti (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
TiO2, Au-loaded TiO2 and Ag-loaded TiO2 nanoparticles were synthesized by the modified sol-gel method together with the impregnation method using titanium tetraisopropoxide (TTIP), ethanol (EtOH), ammonia (NH3) and deionized water as the starting materials. The cellophane membrane was used to control the rate of hydrolysis during sol-gel process. The slow reaction of hydrolysis could produce the small size of TiO2 nanoparticles. HAuCl4 and AgNO3 were used as the precursor for the preparation of Au-loaded TiO2 and Ag-loaded TiO2 nanoparticles, respectively. The amount of Au-loaded and Ag-loaded were in the range of 0.10–3.00 mol%. The crystal structure and crystallinity of TiO2, Au-loaded TiO2 and Ag-loaded TiO2 nanoparticles were examined by an X-ray diffractometry (XRD). Morphologies and particle sizes were investigated by scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HR-TEM). The chemical compositions were examined by energy dispersive X-ray spectrophotometry (EDXS). Specific surface area (SSABET) of the samples was investigated by the Brunauer-Emmett-Teller (BET). The results showed that the TiO2, Au-loaded TiO2 and Ag-loaded TiO2 nanoparticles have spherical shape. Anatase phase of TiO2 was obtained in all samples with an average particle size of 20 nm. The specific surface area was found to be in the range of 60–120 m2/g. The photocatalytic activities of TiO2, Au-loaded TiO2 and Ag-loaded TiO2 nanoparticles were evaluated by studying mineralization of formic acid and oxalic acid under UV-light and visible light illumination by using the setup of spiral photoreactor at Nanoscience Research Laboratory, Faculty of Science, Chiang Mai University. The results showed that Au-loading and Ag-loading could successfully improve the photocatalytic activities of TiO2. Moreover, it was found that Au-loaded TiO2 exhibited a higher mineralization activity than Ag-loaded TiO2 under UV and visible light illumination. For the enhancement of the dye-sensitized solar cells (DSSCs), ITO/TiO2/N-719/electrolyte/Pt, ITO/Au-loaded TiO2/N-719/electrolyte/Pt and ITO/Ag-loaded TiO2/N-719/electrolyte/Pt were fabricated. TiO2 films, Au-loaded TiO2 films and Ag-loaded TiO2 films were deposited on ITO by using squeegee method using EtOH as a solvent and the films were sinterd at 450oC for 30 min before preparation of the cells. Finally, the fabricated cells were studied upon an irradiation of solar light to study the performance and compare the enhancement with the cell fabricated with unloaded TiO2. The fabricated cell with Au-loaded TiO2 and Ag-loaded TiO2 could enhance the conversion efficiency when compared to the fabricated cell with unloaded TiO2. It was found that the performance of the fabricated cells could be enhanced by localized surface plasmon effect and scattering property.